Short‐term water deprivation attenuates the exercise pressor reflex in older female adults. Issue 18 (23rd September 2020) - Watso, Joseph C.; Robinson, Austin T.; Babcock, Matthew C.; Migdal, Kamila U.; Witman, Melissa A. H.; Wenner, Megan M.; Stocker, Sean D.; Farquhar, William B.
Abstract: Older adults have reduced fluid intake and impaired body fluid and electrolyte regulation. Older female adults exhibit exaggerated exercise blood pressure (BP) responses, which is associated with an increased risk of adverse cardiovascular events. However, it is unclear if dysregulated body fluid homeostasis contributes to altered exercise BP responses in older female adults. We tested the hypothesis that short‐term water deprivation (WD) increases exercise BP responses in older female adults. Fifteen female adults (eight young [25 ± 6 years] and seven older [65 ± 6 years]) completed two experimental conditions in random crossover fashion; a euhydration control condition and a stepwise reduction in water intake over three days concluding with a 16‐hr WD period. During both trials, beat‐to‐beat BP (photoplethysmography) and heart rate (electrocardiogram) were continuously assessed during rest, handgrip exercise (30% MVC), and post‐exercise ischemia (metaboreflex isolation). At screening, older compared to young female adults had greater systolic and diastolic BP ( p  ≤ .02). Accelerometer‐assessed habitual physical activity was not different between groups ( p  = .65). Following WD, 24‐hr urine flow rate decreased, whereas thirst, urine specific gravity, and plasma osmolality increased (condition: p  < .05 for all), but these WD‐induced changes were not different between age groups (interaction: p  ≥ .31 for all). Resting systolic and diastolic BP values were higher in older compared to young adults ( p  < .01 for both), but were not different between experimental conditions ( p  ≥ .20). In contrast to our hypothesis, WD was associated with attenuated systolic BP responses during handgrip exercise (post hoc: p  < .01) and post‐exercise ischemia (post hoc: p  = .03) in older, but not young, female adults. These data suggest that reduced water intake‐induced challenges to body fluid homeostasis do not contribute to exaggerated exercise BP responses in post‐menopausal female adults. Abstract : The current data suggest that healthy female aging is associated with a maintained ability to preserve body water balance during short‐term reductions in water intake. These data also indicate that reduced water intake is not associated with augmented cardiovascular responses during exercise pressor reflex activation in older female adults.